Eric Fischl - beach paintings - Fischl, Eric 1948- (Rizzoli, 2009)
Collection of 200 of Eric Fischl's beach-inspired works including paintings, photographs, watercolors, charcoals with a short story by American novelist A. M. Homes.
Keywords: Fischl, Eric / 1948-; Fischl, Eric <1948->; Fischl, Eric -- 1948-; Geschichte 1900-2000; Beaches in art; Nude in art; Figurative painting, American / 20th century; Figurative painting, American / 21st century; Figurative painting, American -- 20th century; Figurative painting, American -- 21st century; Mensch -- Motiv; Malerei; Bildband